Oxidative Stress Activated by Sorafenib Alters the Temozolomide Sensitivity of Human Glioma Cells Through Autophagy and JAK2/STAT3-AIF Axis - Wei, Jianwei; Wang, Zhengfeng; Wang, Weiwei; Liu, Xiaoge; Wan, Junhu; Yuan, Yongjie; Li, Xueyuan; Ma, Liwei; Liu, Xianzhi (Frontiers in Cell and Developmental Biology, 2021)
The development of temozolomide (TMZ) resistance in glioma results in poor prognosis for patients. Sorafenib, a novel diaryl urea compound and multikinase inhibitor, has the ability to effectively cross the blood-brain barrier. However, the effect of sorafenib on glioma cells and the underlying molecular mechanism by which sorafenib enhances the antitumor effects of TMZ remain elusive. Here, we found that sorafenib could enhance the cytotoxic effects of TMZ in glioma cells in vitro and in vivo. Mechanistically, the combination of sorafenib and TMZ induced mitochondrial depolarization and AIF translocation from mitochondria to nucleus, which was depend on STAT3 activation. Moreover, the combination of sorafenib and TMZ inhibited the phosphorylation of JAK2/STAT3 and STAT3 translocation to mitochondria. Inhibition of STAT3 activation promoted the combination of sorafenib and TMZ-induced autophagy-associated apoptosis. Furthermore, the combination of sorafenib and TMZ induced oxidative stress, and ROS clearance reversed the combination of sorafenib and TMZ-mediated JAK2/STAT3 inhibition. Collectively, sorafenib enhanced temozolomide sensitivity of human glioma cells via induction of oxidative stress-mediated STAT3-regluted autophagy and nuclear translocation of AIF.